ESTIMASI NILAI EKONOMI TOTAL (TOTAL ECONOMIC VALUE) SUMBERDAYA ALAM DAN LINGKUNGAN DANAU SINGKARAK - Idris, Idris (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract Lake Singkarak is one of natural resources and environmental which is important for human life. It is located in West Sumatera Province, with area of 11220 km2 and 136 m depth. Until 2000, there were no studies about the total economic value of lake Singkarak resource. That is the reason why the researcher wants to conduct a research to estimate the use value and non-use value of it. In order to quantify the value above, he used some approaches that based on the concept of individual willingness to pay, by using the framework of the total economic value. The study shows that total economic value of natural resources and environmental of Singkarak lake is Rp. 174.950 billion per year. It consists of (a) the economic value of fishery Rp. 7,328 billion, (b) the economic value of irrigation Rp. 0, 775 billion, (c) the economic value of recreation Rp. 4,176 billion, (d) the economic value of domestic use Rp. 7,718 billion, and (e) the the economic value of electricity power Rp. 154,992 billion. These findings are usefull for the government as the policy maker to manage the development of lake Singkarak’s natural resources and its environmental efectively and sustainability.
Keywords: Key word : natural resources and environmental, total economic value, use value, non-use value, willingness to pay